Durabilitas Campuran Hot Rolled Sheet-Wearing Course (HRS-WC) Akibat Rendaman Menerus dan Berkalan Air Rob - ., Nahyo; ., Sudarno; Setiadji, Bagus Hario (Fakultas Teknik Universitas Tanjungpura, 2014)
Tide phenomenon that often occurs in the coastal areas of Indonesia resulted in flooding, which is called the tidal flood. A tidal flood overflow phenomenon of sea water inland. Often some of the roads located in coastal areas are flooded by tidal flood and often causing some damages to the road. Therefore it is necessary to investigate the effect caused by tidal inundation or water bath for asphalt pavement. This research aims to know the durability performance of asphalt concrete mixtures with marinade modification Marshall. The study was conducted with two standard methods of soaking in tidal water and laboratory. Water Immersion method is made by soaking continuous (continuous) and periodic (intermittent). Soaking the specimen in water tidal variation within 6 hours; 12 hours; 24 hours; 48 hours; and 72 hours. While the periodic immersion done by soaking the specimen for 12 hours, then removed during the next 12 hours during 3-days. To view the durability performance of asphalt concrete mixtures used indicator Index of Retained Stability (IRS), Stability Deformation Index, namely First Durability Index (IDP), and the Second Durability Index (IDK). The results showed that continuous immersion damage effects mix quicker on asphalt mixtures than regular immersion. Tidal water used to soak the asphalt mixture Hot Rolled Sheet-Wearing Course (HRS-WC) either continuous or periodic method, has a greater influence than the use of laboratory water. It is shown by the value of the durability of asphalt mixture soaked-tidal water smaller than water-soaked asphalt mixture laboratory standards. Keywords : tidal flood, immersion , durability.